Sick building syndrome (Faculty of Medicine Universitas Indonesia, 2002)
Sick building syndrome describes a number of mostly unspesific complaints of some occupants of the building. The exact pathophysiological mechanism remains elusive. It is a multi factorial event which may include physical, chemical, biological as well as psycological factors. In many cases it is due to insufficient maintenance of the HVAC (heating, ventilation, air conditioning) system in the building. Sign and symptoms can be uncomfortable and even disabling, which may include mucus membrane irritation, neurotoxic symptoms, asthma like symptoms, skin complaints, gastrointestinal symptoms and other related symptoms. There are various investigation methods to diagnose sick building syndrome, and on site assessment of the building is extremely useful. Prevention through a proactive air quality monitoring program is far more desirable than dealing with an actual sick building. Indoor air and the sick building symdrome serves as a paradigm of modern occupational and environmental medicine. (Med J Indones 2002; 11:124-31)Keywords: indoor air pollution, sick building syndrome, building related illness